Lexical synaesthesia in metaphorical collocations - Jurčević, Jana (Vestnik za tuje jezike, 2024)
This study seeks to shed more light on the role of lexical synaesthesia (LS), a phenomenon exem-plified by expressing one sense in terms of another (e.g., gustation for sound – a sweet melody), in the process of forming metaphorical collocations. Lexical synaesthesia is a fascinating intersection of sensory perception and linguistic expression, the investigation of which has proved to be signif-icant for several reasons. Namely, it points to the complex workings of human conceptualization This study seeks to shed more light on the role of lexical synaesthesia (LS), a phenomenon exem-plified by expressing one sense in terms of another (e.g., gustation for sound – a sweet melody), in the process of forming metaphorical collocations. Lexical synaesthesia is a fascinating intersection of sensory perception and linguistic expression, the investigation of which has proved to be signif-icant for several reasons. Namely, it points to the complex workings of human conceptualization the relevance of the embodied nature of language, and subsequently shows ways in which it affects the formation of collocational bonds. This notion came to the foreground when example analysis indicated that LS and metaphorical collocations are both motivated and enabled by the same cog-nitive processes: metonymy and metaphor. To investigate these phenomena closely, we conducted corpus-driven research to extrapolate examples of metaphorical collocations pertaining to the hu-man senses. By analyzing a wide range of corpus data (enTenTen20), we aimed to uncover pat-terns and tendencies in how different senses are interrelated linguistically. The semantic analysis provided insight into the directionality of cross-modal mappings and information on semantically motivated collocational bonding in the field of human sensory experience. Our findings indicate that metaphorical collocations represent a preferred form of LS, with collocational bonds enabled by cross-modal mappings stemming from conceptual metonymy and primary metaphors. Moreo-ver, collocational bonding in LS reaches the highest degree of semantic cohesion between colloca-tional constituents when idioms are formed, as reflected in the low level of substitutability of the collocate. Based on corpus and lexical-semantic analysis, it has been concluded that metaphorical collocations present a useful category in investigations of semantic change, human cognition, con-ceptualization, and perception.
Keywords: cross-modal mappings; embodiment; leksikalna sinestezija; lexical synaesthesia; medmodalne preslikave; metaforične kolokacije; metaphorical collocations; metonimija; metonymy; utelešenje